Social Development from Nuclear and Other Energy: A Myth or Reality from Indonesia - Suratman, Maman; Zainal, Nurazilah (International Journal of Energy Economics and Policy, 2021)
The purpose of this research in Indonesia is to explore the trends and patterns of social development defined by the energy sources during the time of 1985-2017 with a range of statistical methods and procedures. The above stated purpose is addressed with the help of multiple regression methods which is the most cited measure for examining the determinantal impact of independent variables on dependent variables. Therefore, this study has utilized the same method where results are provided in five different 4 different tables. As a complementary work, descriptive measures for example, athematic mean, standard deviation of the mean, and minimum maximum values during the study period are also presented and explained. Both positive and negative influence of energy factors on all five social development measures is examined, however, four out of five measures of social development are found to be insignificant when the effect of fossil fuel is tested. Addition to this, alternative and nuclear energy is positively defining the vulnerable employment of male and females, and negatively affecting the labor force participation and Life expectancy at birth, female (years). The research is suggested to the department of social development specifically in Indonesia, and country-level administrative authorities while exploring the impact of energy variables on development of Indonesian community. Keywords: social development, energy sources, nuclear energy JEL Classifications: O11, K32, O44 DOI: https://doi.org/10.32479/ijeep.10933